PENGARUH WEBSITE DAN BRANDING DESTINASI WISATA HALAL “MAKAM SYAICHONA MOH. CHOLIL BANGKALAN” TERHADAP MINAT BERKUNJUNG - Putri Azizah Fitriyah Maharani; Muh Syarif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to find out and analyze the influence of the website and branding on the interest of visiting the halal tourist destination of Syaichona Moh's Tomb. Cholil Bangkalan. Research using quantitative methods and data analysis techniques using multiple linear regression. The research population is tourists of the halal tourist destination of Syaichona Moh's Tomb. Cholil Bangkalan. Sampling using purposive sampling technique with 133 respondents. In this study, the primary data was directly obtained from visitors to the halal tourist destination of Syaichona Moh's Tomb. Cholil Bangkalan through the distribution of questionnaires The results of the t (partial) test in the study showed that websites and branding partially had a positive and significant effect on the interest of visiting, so that H1 and H2 were accepted. The results of the F (simultaneous) test stated that simultaneously the website and branding have a significant effect on the interest of visiting. So that H3 is accepted. The result of the determinant coefficient shows that the Adjusted R Square is 0.515, which means that the influence of the website and branding on the interest of visiting is 51.5% and the remaining 48.9% is presented by other independent variables outside this study.